Dual application of β-sitosterol and biochar reduces copper toxicity in bamboo via improved redox homeostasis - Emamverdian, Abolghassem; Lyu, Xinyu; Pehlivan, Necla; Zhang, Li; Sultan, Haider; Li, Yang; Zargar, Meisam (Frontiers in Plant Science, 2025)
IntroductionHeavy metal pollution threatens ecosystems and agriculture, necessitating affordable solutions.MethodsWe evaluated the combined effect of β-sitosterol (Bs, 100 mg L-1) and eucalyptus biochar (Eb, 10%) on bamboo (Sasa kongosanensis f. aureo-striatus) under copper stress (100 and 200 mg L-1 Cu).Results and discussionElevated Cu induced oxidative stress via reactive oxygen species (ROS) and methylglyoxal (MG) impairing photosynthesis, nutrient uptake, and growth. Bs and Eb, individually or combined, enhanced antioxidant activity (SOD, CAT, POD, PAL), glyoxalase cycle efficiency, and osmolyte accumulation (proline, glycine betaine), mitigating oxidative damage. The treatments improved photosynthetic pigments, gas exchange, and water retention while reducing Cu translocation and bioaccumulation. Combined Bs+Eb most effectively lowered Cu levels in roots (36–45%), stems (35–38%), and leaves (24–51%) compared to controls. Nutrient uptake (Fe, Mg, Mn, K, P, Ca) was increased by 12–44% with Eb and 7–25% with Bs alone, yet synergistically by 87–190% with Bs+Eb. Biomass and shoot length were improved by 26–54% under Cu stress. The dual application also reduced electrolyte leakage (41–66%) and MG content (12–19%) while boosting non-enzymatic antioxidants (GSH, AsA) by 67–139%. These results demonstrate that Bs and Eb jointly enhance bamboo tolerance against Cu by improving redox homeostasis, nutrient retention, and stress resilience. This approach offers a sustainable strategy for phytoremediation and soil restoration in Cu-contaminated environments.